ESTETIKA TARI KUKILO GAYA SURAKARTA GUBAHAN S. MARIDI - Resi, Laras Ambika; Maryono, Maryono (Institut Seni Indonesia Surakarta, 2014)
This research aims to uncover the aesthetic meaning of the Kukila dance through anaesthetical review in order to discover and describe: (1) the form of the Surakarta style Kukiladance which includes its theme, dancers, movements, make-up, costumes, music, and dance formation;(2) an explanation of the concept which symbolizes the form of the dance and the responseof the audience; and (3) an explanation of the aesthetic meaning of the Surakarta style Kukiladance. The form of the research is qualitative descriptive. The research uses a holistic approachwhich places the form of the dance or its sensation as the objective factor, the concept or idea whichsymbolizes as the genetic factor, and the response or emotion of the audience as the affective factorin an interactive communicative study. The research places each factor in an equal position as adata source and in the activity of the analysis.The theories used for researching the Kukila dance are: (1) Theories of Aesthetics; (2) Theoriesof Performing Arts; (3) Theories of Symbolism; and (4) Theories of Communication. Themethods used by the writer for collecting the data include: a library study, direct and indirectÂ observation, and interviews with a number of informants. The conclusions drawn, based on theform, symbols, and emotions of the audience, are that aesthetically, the Kukila dance depicts afriendship between two kinds of birds which are agile, lively, and vivacious in character, while itfunctions as entertainment and can be interpreted as having content which is meaningful forcharacter building. In its implementation, the form of the Kukila dance is expressed through theperformance of presentative and representative movements which are agile, lively, and vivacious,and supported by make-up and costumes resembling the appearance of a bird, as well as dynamicmusic, creating a sense of harmony in a high quality work of art. The Kukila dance is essentiallya popular dance which is often learned by children in elementary school and junior high school.Keywords: Kukila dance, aesthetic, and character building.